2018
DOI: 10.1016/j.cjtee.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Response of macrophages in rat skeletal muscle after eccentric exercise

Abstract: PurposeMacrophages are known to be important for healing numerous injured tissues depending on their functional phenotypes in response to different stimuli. The objective of this study was to reveal macrophage phenotypic changes involved in exercise-induced skeletal muscle injury and regeneration.MethodsAdult male Sprague-Dawley rats experienced one session of downhill running (16° decline, 16 m/min) for 90 min. After exercise the blood and soleus muscles were collected at 0 h, 6 h, 12 h, 1 d, 2 d, 3 d, 1 w an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…All these factors can explain fragmentation of EUS fibers observed in histology and a significant reduction of the positively-stained AchE area immediately after VD and persistent until 5 days after VD. In concordance with degeneration of EUS fibers, inflammation, necrosis, and phagocytosis of hind limb striated muscle fibers by monocyte/macrophages has been demonstrated during the first week after VD injury in mice 22 and rats 23 .…”
Section: Discussionsupporting
confidence: 59%
“…All these factors can explain fragmentation of EUS fibers observed in histology and a significant reduction of the positively-stained AchE area immediately after VD and persistent until 5 days after VD. In concordance with degeneration of EUS fibers, inflammation, necrosis, and phagocytosis of hind limb striated muscle fibers by monocyte/macrophages has been demonstrated during the first week after VD injury in mice 22 and rats 23 .…”
Section: Discussionsupporting
confidence: 59%
“…Although acute eccentric exercise is usually used to induce inflammation in skeletal muscle, the inflammatory response induced by exercise usually undergoes a switch process from pro-inflammation to anti-inflammation. Zuo et al (2018) detected the early invasion of pro-inflammatory M1 macrophages at 6 h after eccentric exercise. However, anti-inflammatory M2 macrophages were detected in muscles before 24 h after exercise, which even denied the entire pro-inflammatory M1 phenotype during the early stages of tissue repair.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it has been recognized that the dynamic patterns of the macrophage phenotype in skeletal muscle upon eccentric exercise stimuli play a key role in regulating inflammation and promoting skeletal muscle remodeling after eccentric exercise ( Zuo et al, 2018 ). Concurrently, TRIB3 participates in the regulation of macrophage phenotype and function ( Wang et al, 2012 ; Riera-Borrull et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present preclinical study aimed to evaluate the potential of the melon concentrate on the prevention of damages induced by an eccentric exercise in rats. It is demonstrated that strong and unaccustomed eccentric exercise is associated with muscle damage and DOMS [23,24,[34][35][36][37][38][39]. Eccentric contractions are characterized by the lengthening of the muscle-tendon complex; since fibers do not change in volume when they deform, they reduce in diameter as they increase in length [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%